2020
DOI: 10.1055/s-0040-1708837
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Obstructive Pulmonary Disease in the Intensive Care Unit: Antibiotic Treatment of Severe Chronic Obstructive Pulmonary Disease Exacerbations

Abstract: Patients who suffer from chronic obstructive pulmonary disease (COPD) often experience deterioration of baseline respiratory symptoms, acute exacerbations of COPD (AECOPD), that become more frequent with disease progression. Based on symptom severity, approximately 20% of these patients will require hospitalization. The most common indicators for intensive care unit (ICU) admission have been found to be worsening or impending respiratory failure and hemodynamic instability. Bacterial and viral bronchial infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…One-third of the respiratory infections we describe in this work were not microbiologically documented, and may reflect the high frequency of antibiotic use before admission to the ICU, around 60% in the study by Daubin et al 10 The viruses and bacteria identified in our study appear similar to those described in the literature, with the exception of a lower frequency of Enterobacteria (6.6%) and P. aeruginosa (2.8%). [16][17][18] In a previous study of infectious COPD exacerbations in the ICU, P. aeruginosa was found in 7% of exacerbations. 14 Geographic disparity and local ecology may explain these variations.…”
Section: Discussionmentioning
confidence: 96%
“…One-third of the respiratory infections we describe in this work were not microbiologically documented, and may reflect the high frequency of antibiotic use before admission to the ICU, around 60% in the study by Daubin et al 10 The viruses and bacteria identified in our study appear similar to those described in the literature, with the exception of a lower frequency of Enterobacteria (6.6%) and P. aeruginosa (2.8%). [16][17][18] In a previous study of infectious COPD exacerbations in the ICU, P. aeruginosa was found in 7% of exacerbations. 14 Geographic disparity and local ecology may explain these variations.…”
Section: Discussionmentioning
confidence: 96%
“…Sanjay et al showed that with an increase in the sputum volume, exacerbation with dyspnea, and sputum purulence (Jacobs et al, 2019), the absence of prompt antibiotic therapy can be detrimental for many patients with COPD exacerbations (Sethi and Aaron, 2020). Gupta et al (2020) reported that all COPD patients should be started on empirical antibiotic therapy immediately and that the presence of a Pseudomonas infection should mainly be considered. According to the results of an investigative study, the use of antibiotics for AECOPD patients with no obvious signs of infection is significantly greater than that recommended by the guidelines, although the current guidelines do not recommend antibiotic treatment in these patients (López-Campos et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Early antibiotic therapy for AECOPD patients with infection can effectively reduce short-term mortality, reduce the treatment failure rate, and improve sputum production (Gupta et al, 2020;Lancaster et al, 2020;Sethi and Aaron, 2020). Wang et al (2020) reported that there was no difference in the efficacies between antibiotics and placebo in AECOPD patients without infection (Roede et al, 2007), and there is no consensus on the use of antibiotics in AECOPD patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, the systematic prescription of antibiotics remains controversial, as stated in the latest GOLD recommendations (1). For the ICU population, there is no clear recommendation for antibiotic use (19), and no validated biomarkers have been established to guide prescription (20, 21). Again, previous studies have frequently excluded patients in the ICU (22, 23).…”
Section: Discussionmentioning
confidence: 99%